Green synthesis of zinc oxide particles with apple-derived compounds and their application as catalysts in the transesterification of methyl benzoates - Soliman, Mohamed Mostafa Aboelhassan (2020)
Este trabalho foi financiado pelo Concurso Anual para Projetos de Investigação, Desenvolvimento, Inovação e Criação Artística (IDI&CA) 2019 do Instituto Politécnico de Lisboa. Código de referência IPL/2019/STREAM_ISEL